2001
DOI: 10.1139/z01-084
|View full text |Cite
|
Sign up to set email alerts
|

Eye degeneration in the blind cave-dwelling fish Phreatichthys andruzzii

Abstract: The blind cave-dwelling fish Phreatichthys andruzzii shows rapid eye development, and at a temperature of 29.5°C, maximal eye differentiation is reached 36 h after egg laying. Very rapid eye degeneration then occurs, and a rudimentary and very degenerated ocular cyst is all that remains 1 month later. This may explain why this species has so often been erroneously considered anophthalmic. Ocular degeneration starts with a decrease in the rate of mitosis in the neuroblastic cells of the retinal Anlage. Degenera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 8 publications
0
41
0
Order By: Relevance
“…The adult fishes completely lack eyes, pigments and scales and their metabolic rate is extremely reduced. In particular, the eye is totally regressed 36 h post fertilization and 1 month later there remains only a rudimentary cyst, with loss of the optic nerves and strongly reduced optic lobes (Berti et al, 2001;Stemmer et al, 2015). This degeneration is rather premature compared, for example, with what is known for the blind Mexican cavefish Astyanax mexicanus.…”
Section: Introductionmentioning
confidence: 94%
“…The adult fishes completely lack eyes, pigments and scales and their metabolic rate is extremely reduced. In particular, the eye is totally regressed 36 h post fertilization and 1 month later there remains only a rudimentary cyst, with loss of the optic nerves and strongly reduced optic lobes (Berti et al, 2001;Stemmer et al, 2015). This degeneration is rather premature compared, for example, with what is known for the blind Mexican cavefish Astyanax mexicanus.…”
Section: Introductionmentioning
confidence: 94%
“…Phreatichthys andruzzii is a member of the Cyprinidae family and inhabits subterranean cave systems in desert areas of central Somalia. It is a typical cave-dwelling vertebrate, showing an extreme troglomorphic phenotype with complete anophthalmy, together with the complete absence of optic nerves and chiasma, and an extreme reduction in size of the mesencephalic lobes (Ercolini and Berti, 1975;Berti et al, 2001). We have recently demonstrated that mutations in two widely expressed non-visual opsins, a melanopsin and a teleost multiple tissue (TMT)-opsin orthologue, are responsible for the blind clock phenotype in P. andruzzii (Cavallari et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An unresolved issue in this study is the identification of the sensory modality involved in numerical discrimination. Because P. andruzzii shows a complete anophthalmy (Berti et al, 2001), only the use of another sensory modality can be advocated to explain the results we obtained. The two main candidates are the sense of touch and the lateral line system.…”
Section: Discussionmentioning
confidence: 89%
“…Selective pressures might have acted differently from other fish species, on the one hand reducing the cerebral mass in order to optimize the metabolic consumption of the brain, and on the other hand losing the neural circuits supporting cognitive functions not useful in the cave, such as those necessary to discriminate the larger shoal (Buckingham et al, 2007;Gómez-Laplaza and Gerlai, 2011b;Hager and Helfman, 1991). Phreatichthys andruzzii shows an extreme troglomorphic phenotype, and the complete anophthalmy is accompanied by the complete absence of optic nerves and chiasm and by a strong reduction in the size of the entire brain (Berti et al, 2001;Ercolini and Berti, 1975). Furthermore, the schooling behavior is significantly reduced in the cave forms of Astyanax mexicanus relative to the surface form (Kowalko et al, 2013;Parzefall, 1983).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation